Characterization of the labor in livestock farms and profitability of fodder banks in Esparza, Costa Rica - Sánchez Sarmiento, L.Y. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2007